Clinical characteristics and therapeutic response in patients with Burning Mouth Syndrome: accompanying 2 years - CARVALHO,Vanessa Juliana Gomes (2017)
Abstract Introduction Burning Mouth Syndrome (BMS) is a condition characterized by burning symptom of the oral mucosa in the absence of clinical signs. Its etiology is still unknown and, and to date there is no effective treatment. Purpose The aim of this study was to evaluate patients with BMS profile and the therapies results in a retrospective study. Material and method Clinical and therapeutic data were collected from records of patients with BMS diagnosed between January 2013 to April 2015 at the Clinic of Stomatology Clinic, Faculdade de Odontologia of Universidade de São Paulo, according to the criteria established by the International Headache Society in 2013. The therapies used for BMS control were also evaluated. Result Twelve patients were diagnosed with BMS at this period. All of them were women with a mean age of 61.18 years and the apex of the tongue was the most common affected site and the duration of the burning sensation ranged from 6 months to 25 years. Many therapies were prescribed for BMS control, such as topical capsaicin, topical clonazepan, low level laser therapy and homeopathy. Among the established therapies, capsaicin has immediate effect in reducing symptoms. Conclusion The present study showed that the challenges towards an effective treatment for BMS are varied and are mainly related to the lack knowing of the pathogenesis of this disease. The demographic profile of patients studied here was similar to that described in the available literature, however, the variables represented by secondary symptoms (medical history, anxiety and depression levels) may be modifying factors of therapeutic response and the pathogenesis of the disease itself.